Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3109/0886022x.2012.656559
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Renal Failure Due to Solitary Plasmacytoma: Parenchymal Invasion of the Kidney

Abstract: Solitary extramedullary plasmacytoma (EMP) is a rare plasma cell disorder mostly involving the upper airway; however, retroperitoneal infiltration is very rare. Kidney injury associated with EMP is exceptionally rare with only anecdotal reports. Herein we report a case of retroperitoneal EMP causing renal failure by the way of direct renal parenchymal infiltration. Renal parenchymal invasion should be considered in aggressive and refractory plasma cell dyscrasias with unexplained renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Retroperitoneal plasmacytoma can present with abdominal pain or discomfort, back pain, obstructive jaundice,6 renal failure if there is invasion of the bilateral kidneys 2. Our patient had significant left-sided hydronephrosis, indicating compression of the left ureter by the mass.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Retroperitoneal plasmacytoma can present with abdominal pain or discomfort, back pain, obstructive jaundice,6 renal failure if there is invasion of the bilateral kidneys 2. Our patient had significant left-sided hydronephrosis, indicating compression of the left ureter by the mass.…”
Section: Discussionmentioning
confidence: 68%
“…Owing to the rarity of this entity, epidemiology including prevalence, age and sex distribution has not been well defined in the literature. In published case reports, involvement of variable age groups, ranging from 25 to 70 years, has been described 2 3 5–7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously suggested that dementia with declined cognitive function shows relatively intact emotional functions using the Mini-Emotional State Examination. 1 Dementia is defined as a state of abnormality of brain function resulting in impairment of social function and interaction. If older people gently yielded to their caregiver's advice on activities, such as taking a bath and eating, but without showing BPSD, then this is not a case of dementia, 2 even if cognition is somewhat blurred, perhaps when sitting quietly on the veranda.…”
Section: Core Symptoms and Peripheral Symptoms Of Dementiamentioning
confidence: 99%
“…Retroperitoneal plasmacytoma patients can present with abdominal pain, back pain, discomfort, jaundice, dysuria or renal failure. [1][2][3] Retroperitoneal plasmacytoma develops in an unusual location and causes non-specific symptoms. Although our patient had slight back pain, laboratory analysis did not show renal failure or a rise in the bilirubin level.…”
mentioning
confidence: 99%